Friction and Wear of DLC Coating Deposited on M2 Steel via µW-PECVD Against 100Cr6 Steel with Different Normal Loads and Sliding Speeds Under Dry and Lubrication Conditions - Nay Win Khun; Anne Neville; Ivan Kolev; Hongyuan Zhao (Tribology in Industry)
The friction and wear of diamond-like carbon (DLC) coating deposited on a M2 steel substrate (DLC-Steel) via microwave excited plasma enhanced chemical vapor deposition (µW-PECVD) against a 100Cr6 steel ball without or with an Asian Formulated Oil (AFO) were systematically investigated with different normal loads and sliding speeds. Under a dry condition, the DLC-Steel exhibited an increase in its wear with an increased normal load from 1 to 5 N, while its wear increased with an increased sliding speed from 1 to 3 cm/s and turned to decrease with a further increased sliding speed to 5 cm/s. The increased wear of the DLC-Steel resulted in its increased friction via an increase in contact between two rubbing surfaces during dry sliding. However, the DLC-Steel exhibited a decrease in its friction with an increased normal load or sliding speed under a lubrication condition, although it did not have any measurable wear for all the normal loads and sliding speeds. It could be concluded that the µW-PECVD-DLC coating could effectively prevent its underlying steel substrate from abrasive wear for all the normal loads and sliding speeds under both dry and lubrication conditions.